Sample chamber for synchrotron based in‐situ X‐ray diffraction experiments under electric fields and temperatures between 100 K and 1250 K. (9th December 2020) - Nentwich, Melanie; Weigel, Tina; Richter, Carsten; Stöcker, Hartmut; Mehner, Erik; Jachalke, Sven; Novikov, Dmitri V.; Zschornak, Matthias; Meyer, Dirk C.
Abstract : A custom sample chamber developed for synchrotron X‐ray experiments conducted at varying temperatures combined with the application of electric fields is presented. The chamber features an exchangeable hemispherical dome and an xyz manipulator for electric contacting of the sample. The article describes heating and cooling capabilities, exemplary experiments and plans for future upgrades of the chamber. Abstract : Many scientific questions require X‐ray experiments conducted at varying temperatures, sometimes combined with the application of electric fields. Here, a customized sample chamber developed for beamlines P23 and P24 of PETRA III at DESY to suit these demands is presented. The chamber body consists mainly of standard vacuum parts housing the heater/cooler assembly supplying a temperature range of 100 K to 1250 K and an xyz manipulator holding an electric contact needle for electric measurements at both high voltage and low current. The chamber is closed by an exchangeable hemispherical dome offering all degrees of freedom for single‐crystal experiments within one hemisphere of solid angle. The currently available dome materials (PC, PS, PEEK polymers) differ in their absorption and scattering characteristics, with PEEK providing the best overall performance. The article further describes heating and cooling capabilities, electric characteristics, and plans for future upgrades of the chamber. Examples of applications are discussed.